Krótkoterminowe prognozowanie koniunktury regionalnej za pomocą modelu ADL na przykładzie regionów Stanów Zjednoczonych - Welc, Jacek (Short-term Regional Business Activity Forecasting with the Use of ADL Model in Three Regions of the United States, 2006)
The paper analyses the possibility of applying simple single-equation autoregressive distributed lags models for forecasting regional business activity. The cases of three U.S. states have been used. For each of them the forecasting model has been estimated and analyzed, using data from the 1st quarter of 1975 to the 4Ih quarter of 2003. The yearly change in the level of the non-farm employment has been used as a measure of regional business activity. The analysis confirms that simple models can be a useful forecasting tool, significantly affecting the planning and implementation of the economic policy on a regional level.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 241-249